2022
DOI: 10.3390/ijms231911546
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) Crosses the Blood–Brain Barrier (BBB) and Induces Neuroprotective Effects in the Embryonic Chicken Cerebellum after a Hypoxic Injury

Abstract: Several motor, sensory, cognitive, and behavioral dysfunctions are associated with neural lesions occurring after a hypoxic injury (HI) in preterm infants. Growth hormone (GH) expression is upregulated in several brain areas when exposed to HI conditions, suggesting actions as a local neurotrophic factor. It is known that GH, either exogenous and/or locally expressed, exerts neuroprotective and regenerative actions in cerebellar neurons in response to HI. However, it is still controversial whether GH can cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In this regard, our previous studies demonstrated that Klf13 -deficient hippocampal neurons exhibit increased cell death following glutamate-induced excitotoxicity [ 10 ]. Conversely, both endogenous and administrated GH have been shown to promote cell survival in neurons exposed to various types of injury [ 28 , 47 , 48 , 49 ]. Therefore, while we acknowledge that multiple signaling pathways may be involved in this response, it is possible that the depletion of KLF13 could affect cell death by disrupting the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our previous studies demonstrated that Klf13 -deficient hippocampal neurons exhibit increased cell death following glutamate-induced excitotoxicity [ 10 ]. Conversely, both endogenous and administrated GH have been shown to promote cell survival in neurons exposed to various types of injury [ 28 , 47 , 48 , 49 ]. Therefore, while we acknowledge that multiple signaling pathways may be involved in this response, it is possible that the depletion of KLF13 could affect cell death by disrupting the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…GH has a protective role in establishment and maintenance of the BBB during development and in the neonatal brain, especially in models of hypoxia-induced injury ( 247 249 ). Recombinant human GH (rhGH) has been shown to have a protective effect in a mouse model of neonatal hypoxic brain injury.…”
Section: Role Of Gh/igf-1 In Regulation Of Cerebrovascular Functionmentioning
confidence: 99%